Role of LOC_Os01g68450, Containing DUF2358, in Salt Tolerance Is Mediated via Adaptation of Absorbed Light Energy Dissipation - Chutarat Punchkhon; Panita Chutimanukul; Ratchata Chokwiwatkul; Triono Bagus Saputro; Aleel K. Grennan; Nuria De Diego; Lukáš Spíchal; Supachitra Chadchawan (Plants, 2022)
Salt stress affects plant growth and productivity. In this study we determined the roles of eight genes involved in photosynthesis, using gene co-expression network analysis, under salt-stress conditions using Arabidopsis knockout mutants. The green area of the leaves was minimum in the at1g65230 mutant line. Rice LOC_Os01g68450, a homolog of at1g65230, was ectopically expressed in the at1g65230 mutant line to generate revertant lines. Under salt stress, the revertant lines exhibited significantly higher net photosynthesis rates than the at1g65230 mutant line. Moreover, the operating efficiency of photosystem II (PSII) and electron transport rate of the revertant lines were higher than those of the wild type and at1g65230 mutant line after 10 days of exposure to salt stress. After this period, the protein PsbD–the component of PSII–decreased in all lines tested without significant difference among them. However, the chlorophyll a and b, carotenoid, and anthocyanin contents of revertant lines were higher than those of the mutant line. Furthermore, lower maximum chlorophyll fluorescence was detected in the revertant lines. This suggests that LOC_Os01g68450 expression contributed to the salt tolerance phenotype by modifying the energy dissipation process and led to the ability to maintain photosynthesis under salt stress conditions.